COURTS AS ACTORS OF ADMINISTRATIVE JURISDICTION - Гончарук, С. Т. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article reveals the concept and content of administrative and jurisdictional functions of local courts of Ukraine, analyzes separate problems of this type of judicial activity at the present stage, makes some generalizations and conclusions and makes suggestions for its improvement.